Analisis Pertumbuhan Ekonomi Kawasan Sentra Produksi Subsektor Tanaman Pangan di Provinsi Sumatera Barat - Fastabiqul Khairad; Melinda Noer; Mahdi Mahdi (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2018)
This study aims to analyze economic growth of production centers of leading agricultural commodities food crops in West Sumatera Province. The data used in this study are secondary data with descriptive analysis tool by comparing the economic growth: GDP, agricultural sector and food crop subsector in West Sumatera Province before and after the establishment of production centers for food commodities. The productivity level of leading agricultural commodities in each region that has been determined tends to fluctuate and have not always increased. The rate of economic growth reflected in GDP of the food crops actually decreased significantly from 2014 to 2016. This illustrates that the establishment of production center areas has not fully been able to increase the productivity of production centers nor increase the economic growth of food crops subsector, agricultural sector and the overall economic growth rate in West Sumatera Province.